ACCEPTANCE AND RETURN SYSTEM ADMINISTRATION SERVICES IN LAUNDRY CHEMICAL LAUNDRY SURYA - Fahrul Rizal; Jalinas Jalinas, Skom, MM (Jurnal Sistem Informasi, 2004)
In a small and large companies require the admissions process really accurate than thedata of each consumer begins receiving means until the return of consumeracceptance in the demand for services that it is definitely different every receiptobtained from the consumer.Therefore acceptance conducted in a computer system it is helpful to process thefinancial administration in this case a "Surya Chemicals Laundry Laundry" need touse a computer from a manual to computerized processes because consumers willrequire more effective and efficient.